The Role of Job Satisfaction in Mediating Human Resource Management Practices and Organizational Culture on Organizational Performance - Febrina, Sindy Cahya (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study aims to determine the effect of human resource management practices and organizational culture on organizational performance through job satisfaction. The number of samples used were employees of Bank Rakyat Indonesia Malang City, for the sampling technique using saturated sampling. Data collection through questionnaires, with the Structural Equation Modeling (SEM) data analysis method. The results of the study showed: 1) Human resource management practices have a significant effect on job satisfaction; 2) Human resource practices do not have a significant effect on organizational performance; 3) Organizational culture has a significant effect on job satisfaction; 4) Organizational culture has a significant effect on organizational performance; 5) Job satisfaction has a significant effect on organizational performance; 6) Human resource management practices and organizational culture have a significant effect on organizational performance through job satisfaction.